Factors Affecting Implementation of Blockchain in Retail Market in Malaysia - Mahadi Hasan Miraz; Mohamad Ghozali Hassan; Kamal Imran Mohd Sharif (International Journal of Supply Chain Management, 2020)
Certain types of blockchains were made and developed for various purposes. Despite the development of cohort systems, the blockchain needs more development from the perspective of Malaysia. In addition, blockchain is the only cryptographic block currency that improves retail marketing. This study has critically analyzed the variables of the current research Framework of the blockchain implementation in retail market. Thus, this study aims to implement blockchain in retail market for increaseing customer benefits in order to improve the retail industrial supply chain activities. In order to achieve the main aim, this study comprises of two main phases, which are theoretical study, development of proposed blockchain factors and its implementation. The blockchain experience of variables, blockchain management, blockchain transaction policy, blockchain adaption and implications were discussed gradually. Finally, we demonstrate the underlying theory, the theoretical framework and the hypotheses were discussed in detail.